Nonsmooth and nonlocal differential equations in lattice-ordered Banach spaces. (12th June 2005) - Carl, Siegfried; Heikkilä, S.
Abstract : We derive existence results for initial and boundary value problems in lattice-ordered Banach spaces. The considered problems can be singular, functional, discontinuous, and nonlocal. Concrete examples are also solved.